Caught between Orientalism and Aryanism, exile and homeland: The Jews of Iran in Zionist/Israeli imagination - Haggai, Ram (Hagar: Studies in Society and Culture, 2008)
This article provides a first-of-a-kind examination of Zionism and the Jewish state’s shifting and unstable perceptions of Iranian Jewry, a particularly important Mizrahi group that has not yet received the attention it deserves in critical scholarship. By focusing on Iranian Jewry as objects of the Zionist/Israeli gaze, I demonstrate that while notions of "exile" and "homeland" and "East" and "West" have been known to be notoriously axiomatic and rigid when applied to Jews from the Arab countries, they appear fluid, overlapping and contingent when applied to Iran’s Jews. As I demonstrate, owing to the twofold issue of ascribed ethnicity and distinctive history, Iran’s Jews-perhaps more than any other Jewish "diaspora"-confounded the most fundamental Zionist convictions embodied in the notion of the "ingathering of exiles."